Im Schatten der Arbeitsgesellschaft : Arbeitslose und die Dynamik sozialer Ausgrenzung - Kronauer, Martin; Vogel, Berthold; Gerlach, Frank (Frankfurt am Main : Campus Verlag, 1993)
BMLIK
Duits
Monografie
Keywords: werkloosheid